2013
DOI: 10.1007/s10162-013-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Auditory Responses in the Inferior Colliculus in a Heterogeneous Manner

Abstract: Perception of complex sounds such as speech is affected by a variety of factors, including attention, expectation of reward, physiological state, and/or disorders, yet the mechanisms underlying this modulation are not well understood. Although dopamine is commonly studied for its role in reward-based learning and in disorders, multiple lines of evidence suggest that dopamine is also involved in modulating auditory processing. In this study, we examined the effects of dopamine application on neuronal response p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 69 publications
(52 reference statements)
4
60
0
Order By: Relevance
“…Neuromodulatory influences to the IC include those mediated by noradrenergic (Hormigo, Horta Junior Jde, Gomez-Nieto, & Lopez, 2012;Klepper & Herbert, 1991), serotoninergic (Hurley & Sullivan, 2012;Obara, Kamiya, & Fukuda, 2014;Ramsey, Sinha, & Hurley, 2010;Thompson & Thompson, 2009), dopaminergic (Gittelman, Perkel, & Portfors, 2013;Olazabal & Moore, 1989) and cholinergic projections (Schofield, 2010). The cholinergic inputs originate in the pontomesencephalic tegmentum, that includes the pedunculopontine and laterodorsal tegmental nucleus.…”
Section: Excitatory Inhibitory and Cholinergic Inputs To The Icmentioning
confidence: 97%
“…Neuromodulatory influences to the IC include those mediated by noradrenergic (Hormigo, Horta Junior Jde, Gomez-Nieto, & Lopez, 2012;Klepper & Herbert, 1991), serotoninergic (Hurley & Sullivan, 2012;Obara, Kamiya, & Fukuda, 2014;Ramsey, Sinha, & Hurley, 2010;Thompson & Thompson, 2009), dopaminergic (Gittelman, Perkel, & Portfors, 2013;Olazabal & Moore, 1989) and cholinergic projections (Schofield, 2010). The cholinergic inputs originate in the pontomesencephalic tegmentum, that includes the pedunculopontine and laterodorsal tegmental nucleus.…”
Section: Excitatory Inhibitory and Cholinergic Inputs To The Icmentioning
confidence: 97%
“…A variety of studies have provided intriguing data suggesting that the neuromodulator dopamine plays an important role in modulating auditory responses. For example, Bender et al (2010) showed that dopamine can modulate action potential initiation in the dorsal cochlear nucleus and Gittelman et al (2013) showed that dopamine heterogeneously modulates response properties of neurons in the inferior colliculus (IC). Moreover, people with Parkinson’s disease and schizophrenia, both disorders characterized by a dysfunction in dopamine signaling, have speech processing problems (Gräber et al, 2002; Schröder et al, 2010; Kantrowitz et al, 2015) and people with schizophrenia may experience auditory hallucinations (Lennox et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DAergic and/or NAergic input may function to alter temporal encoding and frequency discrimination in a complex naturalistic sound field (see Hurley et al, 2004). Recently, Gittelman et al (2013) demonstrated both excitatory and inhibitory DA modulation of auditory responses in IC of mice and there is evidence for NE-induced suppression of IC neuronal response in the bat (Hurley et al, 2004). Less is known about behavioral implications of CA action in the auditory midbrain although manipulating DA receptor activation in IC of rats disrupts acoustic startle-mediated prepulse inhibition (Satake et al, 2012).…”
Section: Th-ir Innervation Of Central Auditory Circuitry-likementioning
confidence: 99%